Spiralians in the limelight: meeting report - Arendt, Detlev (Genome biology, 2003)
A report on the meeting 'Developmental Basis of Evolutionary Change', Usc perniversity of Chicago, USA, 16-18 October 2003
Gesehen am 23.06.2017
Keywords: Konferenzschrift